1976
DOI: 10.1084/jem.144.3.713
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the antigen-specific suppressive T-cell factor in the regulation of antibody response of the mouse. IV. Special subregion assignment of the gene(s) that codes for the suppressive T-cell factor in the H-2 histocompatibility complex.

Abstract: The locus of the gene that codes for the antigen-specific suppressive T-cell factor was determined to be in a new subregion "I-J" which locates between I-B and I-C subregions in the H-2 histocompatibility complex. This was shown by two different lines of evidence: (a) The absorbing capacity for the suppressive T-cell factor of several alloantisera against restricted I subregions did not correlate with their specificity for previously known Ia molecules which are coded for by genes in I-A and I-C subregions, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
3
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(150 citation statements)
references
References 24 publications
9
137
3
1
Order By: Relevance
“…cluding helper T-cell-replacing factors (17,18) and suppressor factors (19,20). These molecules share certain properties: mol wt of approximately 50,000, antigen-binding sites, the lack of Ig determinants, and the presence of determinants recognized by alloantisera specific for I-region gene products.…”
Section: Discussionmentioning
confidence: 99%
“…cluding helper T-cell-replacing factors (17,18) and suppressor factors (19,20). These molecules share certain properties: mol wt of approximately 50,000, antigen-binding sites, the lack of Ig determinants, and the presence of determinants recognized by alloantisera specific for I-region gene products.…”
Section: Discussionmentioning
confidence: 99%
“…These two Ts cell systems, although independent phenomena, shared some characteristics; both are examples of Ts cells not restricted by the I-J subregion of the H-2 complex, in contrast to antigen specific Ts cells (24,25). These Ts cells, however, are stimulated and interact with target cells in a genetically restricted manner controlled by the I-A subregions.…”
Section: Genetic Restrictions On Haplotype-specific Ts Cell Activitymentioning
confidence: 99%
“…Thirdly, our previous studies (3,8,22,24) have demonstrated that various alloantibodies directed against I-J products have the capacity to absorb the KLH-specific suppressor factors from primed splenic T cells and KLH=specific suppressor hybridomas. Similar observations have been reported by several other investigators with different systems (reviewed in 2).…”
Section: Discussionmentioning
confidence: 99%